Effectiveness of a Perioperative Pediatric Nursing Intervention with a Brazilian Educational Comic Book: A Quasi-Experimental Study - Mizobata, Vanessa Natsumi [UNESP]; Teixeira, Tatiane Roberta Fernandes [UNESP]; Crepalde, Patricia Aparecida Francelino [UNESP]; Minharro, Michelle Cristine De Oliveira [UNESP]; Avila, Marla Andreia Garcia de [UNESP] (Sage Publications Inc, 2025)
Purpose: This study aimed to compare an educational intervention with an educational comic book and oral information versus oral information alone, for 45 children and their parents before pediatric surgery. Design and Methods: A quasi-experimental study was conducted at a public university in Brazil. The content of the comic book was previously validated, and its face validity for use in children's perioperative care was previously confirmed. Inclusion criteria were children aged 6 to 14 years, American Society of Anesthesiologists physical status classification I or II, undergoing their first elective surgical procedure, and literate parents. A questionnaire was used to collect data on the sociodemographic characteristics of the children and their parents. A questionnaire was administered to children aged 6 to 10 years, another for those aged 11 to 14 years, and a third for parents to evaluate their knowledge about surgery. Results: The sociodemographic characteristics of the intervention group (N = 22) and the control group (N = 23) were comparable. In both groups, for both the children and their parents, there was a significant difference between pre- and post-orientation knowledge scores. However, there was no difference in knowledge scores between the two educational strategies. Conclusion: Educational interventions on the day of surgery are beneficial for increasing knowledge among patients and family members, regardless of the method used. We recommended the process of preparing the child should begin after scheduling the surgery, and nurses should use a child-centered care approach.
Keywords: children; health literacy; parents; perioperative nursing